In-situ phase separation copolymer solid electrolyte and preparation method thereof

The in-situ phase separation copolymer solid electrolyte is prepared by in-situ one-step method, which solves the problem that electrolytes in the prior art is difficult to achieve high ion conductivity and high mechanical strength, and realizes an efficient and low-cost preparation method, which is suitable for commercial battery production.

CN119708378AActive Publication Date: 2025-03-28SUN YAT SEN UNIV

Patent Information

Application Number
CN202510039886.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-10
Publication Date
2025-03-28
Estimated Expiration
2045-01-10

AI Technical Summary

Technical Problem

In existing solid-state lithium batteries, it is difficult for electrolytes to achieve high ion conductivity and high mechanical strength at the same time, and the preparation process is high and the steps are complicated.

Method used

In situ phase separation copolymer solid electrolyte is prepared by in-situ one-step method. The reaction of soft and hard section monomers under different salt/solvent systems is carried out, and the P (AAM-co-MPEGA) copolymer electrolyte is formed by heat-induced polymerization or photo-induced polymerization to achieve both high ionic conductivity and high mechanical strength.

Benefits of technology

The copolymer electrolyte with high ion conductivity and high mechanical strength is achieved, which reduces the production cost and step complexity, is suitable for commercial battery production lines, and improves the energy density and safety performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119708378A_ABST
    Figure CN119708378A_ABST
Patent Text Reader

Abstract

The invention discloses an in-situ phase separation copolymer solid electrolyte and a preparation method thereof. An alkenyl monomer capable of forming a strong hydrogen-bond interaction is used as a hard segment monomer, acrylamide is used as a representative, the strong hydrogen-bond interaction can be formed among PAAm chain segments formed after the acrylamide participates in copolymerization, and mechanical support is provided as a hard phase; an alkenyl monomer with a side chain containing ether is used as a soft segment monomer, methoxy poly (ethylene glycol) acrylate is used as a representative, and a PMPEGA chain segment formed after the methoxy poly (ethylene glycol) acrylate participates in copolymerization has long side chain ether, can enrich a solvent and a lithium salt, and is used as an ion conduction phase to rapidly conduct lithium ions. The two monomers and the lithium salt can be dissolved in different solvent systems, and can be subjected to in-situ thermal initiation polymerization in the battery or photo-initiation polymerization on the surface of an electrode to generate a copolymer electrolyte. The in-situ phase separation copolymer solid electrolyte prepared by the invention simultaneously realizes high ionic conductivity and high mechanical strength, and the preparation method is simple and easy to implement, and is suitable for a production process of assembling first and then injecting liquid of a current commercial liquid battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of solid electrolytes, and in particular relates to an in-situ phase separation copolymer solid electrolyte and a preparation method thereof. Background Art

[0002] Solid-state lithium metal batteries use ultra-high specific capacity (3860 mAh / g) lithium metal as the negative electrode, matched with ultra-thin high-performance solid electrolytes, and can achieve the goal of 500 Wh / Kg. Solid electrolytes replace leaky, flammable and explosive electrolytes, and are expected to achieve breakthroughs in battery safety performance and energy density.

[0003] The key issues restricting the development of high-energy solid-state lithium batteries are: (1) It is not possible to have both high ionic conductivity and high mechanical strength of the electrolyte: Inorganic solid electrolytes have high ionic conductivity but are hard and brittle; the complexation-decomplexation ion-conducting mechanism of polymer electrolytes requires that the polymer ion-conducting region be in a highly elastic state, which limits the simultaneous improvement of ionic conductivity and strength, and limits the energy density and safety performance of solid-state batteries; (2) The problem of high cost of electrolyte preparation process: Inorganic solid electrolytes require high-temperature synthesis and GPa-level high-pressure compaction; most polymer electrolytes are prepared by solvent evaporation of "polymer-lithium salt solution", which needs to be carried out under oxygen and moisture-proof conditions, which is time-consuming, energy-consuming, and pollutes the environment. The mechanical strength is also difficult to meet the requirements of large-scale roll-to-roll preparation, and is not suitable for existing lithium battery production lines.

[0004] Solid electrolytes can be divided into inorganic solid electrolytes, solid polymer electrolytes and organic-inorganic composite electrolytes. Inorganic solid electrolytes are mainly divided into two categories: oxide electrolytes and sulfide electrolytes. Their advantage is that they have high ionic conductivity comparable to liquid. However, these inorganic solid electrolytes generally have the following disadvantages: ① generally poor chemical stability: sensitive to water and oxygen, unstable to metallic lithium; ② significant electrode interface problems: inorganic solid electrolytes are hard and brittle, the positive and negative electrode interfaces are poorly contacted, and cracks and holes are easily generated at the interface, which hinder the transmission of lithium ions and induce the growth of lithium dendrites; ③ high cost and difficult manufacturing: inorganic electrolytes are expensive; lack of flexibility, and GPa-level pressure is required to ensure the compactness of the battery. The organic-inorganic composite electrolyte has large differences in the properties of the two phases, and there are new interface problems. Particle agglomeration often occurs, resulting in low ion conductivity and poor yield; the interface of the lithium negative electrode / electrolyte still has the difference between hard contact and soft contact and the problem of uneven ion conduction causing lithium dendrite growth. In contrast, polymer electrolytes have advantages in all three aspects: ① Chemical stability is better than that of inorganic solid electrolytes: they are relatively inert and insensitive to water and oxygen; ② High electrode interface compatibility: polymer electrolytes have viscoelasticity and can form an adaptive electrode / electrolyte interface; ③ Low manufacturing cost, and it is expected to achieve roll-to-roll large-scale production: polymer electrolytes are lightweight, and the monomer raw materials are usually cheap and widely available; they have good mechanical flexibility and are easy to form films, and roll-to-roll preparation is suitable for the current commercial battery "assembly first, then injection" production process.

[0005] The Chinese invention patent with application number 2022106485496 and titled "A polyurethane-based polymer solid electrolyte material and its preparation method and application" uses hard segments and soft segments to form polyurethane-based polymer solid electrolyte materials under the action of hydrogen bonds. However, the two-block or tri-block copolymer electrolyte of polyurethane in this patent is at least a several-step process, and at the same time, such a copolymer is obtained by reaction with the participation of solvent, and then it is blended with lithium salt by melting or solvent method to obtain a polymer electrolyte, and then the third step of non-in-situ assembly with battery is formed to form a solid-state battery. The whole process is very time-consuming and labor-intensive, and diisocyanate is very expensive, and there are a series of cumbersome steps such as solvent treatment. Summary of the invention

[0006] The purpose of the present invention is to overcome the shortcomings of the prior art and provide an in-situ one-pot one-step method for preparing an in-situ phase-separated copolymer solid electrolyte and a preparation method thereof. The present invention can generate a solid-state battery by in-situ polymerization inside a battery, thereby avoiding battery short circuit, having low cost and simple steps; and at the same time, solving the contradiction between high ionic conductivity and high mechanical strength.

[0007] The above-mentioned purpose of the present invention is solved by the following technical methods: In order to achieve the effect of in-situ preparation of polymer electrolytes and separation of high ionic conductivity and high mechanical strength, the present invention adopts an in-situ one-pot one-step method, utilizing the differences in reaction rates and compatibilities of soft and hard segment monomers in different salt / solvent systems to design and prepare phase-separated polymer electrolytes by thermally initiated polymerization and photoinitiated polymerization.

[0008] The in-situ phase separation copolymer solid electrolyte of the present invention uses an olefinic monomer capable of forming a strong hydrogen bond as a hard segment monomer, preferably represented by acrylamide (AAm), and the PAAm segments formed after the copolymerization thereof can form a strong hydrogen bond, exclude solvents and lithium salts, and provide mechanical support as a hard phase; an olefinic monomer containing an ether in the side chain is used as a soft segment monomer, preferably represented by methoxy poly (ethylene glycol) acrylate (MPEGA), and the PMPEGA segments formed after the copolymerization thereof have long side chain ethers, and the large steric hindrance can reduce the regularity of the segments, and have a high proportion of free volume, thereby reducing the glass transition temperature ( T g ), which can enrich solvents and lithium salts and quickly conduct lithium ions as an ion-conducting phase. These two monomers and lithium salts can be dissolved in different solvent systems and can be thermally initiated and polymerized in situ inside the battery or photoinitiated and polymerized on the electrode surface in a one-pot, one-step process to generate P(AAM- co -MPEGA) copolymer electrolyte. The composition and nomenclature of the copolymer electrolyte are as follows: P(AAM 0.8 - co -MPEGA 0.2 )+ 70 wt% 1M LiTFSI / FEC, abbreviated as AM-87@FEC, A and M are the initials of the two monomers, 8 represents that the hard segment AAm accounts for 80 wt% in the polymer, and 7 represents that 1 MLiTFSI / FEC accounts for 70 wt% in the whole polymer electrolyte.

[0009] An in-situ phase separation copolymer solid electrolyte is prepared by using an olefin monomer capable of forming strong hydrogen bonds as a hard segment monomer and an olefin monomer with an ether-containing side group as a soft segment monomer. These two monomers and a lithium salt are dissolved in a solvent system and polymerized by heat or light in the presence of a crosslinking agent.

[0010] Preferably, in the above-mentioned in-situ phase separation copolymer solid electrolyte, the hard segment monomer is as shown in formula (I):

[0011] Preferably, in the above-mentioned in-situ phase separation copolymer solid electrolyte, the soft segment monomer is as shown in formula (II), wherein x is the number of links, and the value is 1-50:

[0012] Preferably, in the above-mentioned in-situ phase separation copolymer solid electrolyte, the solvent is a nitrile solvent, an ether solvent, a carbonate solvent or a phosphate solvent.

[0013] Preferably, in the above-mentioned in-situ phase separation copolymer solid electrolyte, the lithium salt is as shown in formula (III):

[0014] Preferably, in the above-mentioned in-situ phase-separated copolymer solid electrolyte, the mass percentage of the copolymer formed by the hard segment and the soft segment in the in-situ phase-separated copolymer solid electrolyte is 25-90%.

[0015] Preferably, in the above-mentioned in-situ phase separation copolymer solid electrolyte, the ratio of the hard segment monomer to the total mass of the soft segment and hard segment monomer is 5-100%.

[0016] Preferably, in the above-mentioned in-situ phase separation copolymer solid electrolyte, the crosslinking agent contains two or more carbon-carbon double bonds and can react to form a crosslinked network, such as a diene, triene or tetraene monomer.

[0017] Compared with the prior art, the present invention has the following beneficial effects: 1. The in-situ phase-separated copolymer solid electrolyte prepared by the present invention achieves both high ionic conductivity and high mechanical strength. The ionic conductivity of AM-87@FEC electrolyte is as high as 1.6 mS / cm at 28°C, the tensile strength is 5.07 MPa, the compressive strength is 10.86 MPa, and the elastic modulus is 22.79 MPa; the ionic conductivity of AM-67@SN electrolyte is as high as 1.5 mS / cm at 28°C, the tensile strength is 3.96 MPa, the compressive strength is 7.10 MPa, and the elastic modulus is 76.4 MPa; the ionic conductivity of AM-87@SN electrolyte also reaches 0.61 mS / cm at 28°C, the tensile strength is 5.04 MPa, and the elastic modulus is 124 MPa; among them, the high modulus polymer electrolyte plays a key role in inhibiting the growth of lithium dendrites, and also reduces the risk of short circuit, ensuring the safety of the battery.

[0018] 2. The preparation method of the present invention is simple and easy, and the copolymer electrolyte can be obtained by in-situ polymerization inside the battery through a one-pot one-step method, which is suitable for the current commercial liquid battery "assembly first, then injection" production process. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 The preparation flow chart of Example 2, Example 3 and Example 4 is shown.

[0020] Figure 2This is the impedance diagram measured for the AM-xy@SN copolymer solid electrolyte in Example 5.

[0021] Figure 3 This is the ionic conductivity diagram obtained for the AM-xy@SN copolymer solid electrolyte in Example 5.

[0022] Figure 4 This is the ionic conductivity diagram obtained for the AM-xy@LDN copolymer solid electrolyte in Example 5.

[0023] Figure 5 This is the ionic conductivity diagram obtained for the AM-xy@FEC copolymer solid electrolyte in Example 5.

[0024] Figure 6 This is the tensile strength diagram of AM-xy@SN measured in Example 6.

[0025] Figure 7 This is the tensile strength diagram of AM-xy@FEC measured in Example 6.

[0026] Figure 8 Graph showing the relationship between the tensile strength and ionic conductivity of the AM-xy@SN obtained in Examples 5 and 6.

[0027] Fig. 9 1 is a relationship diagram between the tensile strength and ionic conductivity of the AM-xy@FEC obtained in Example 5 and Example 6.

[0028] Fig.10 This is the AM-xy@FEC spline diagram used to measure the tensile strength in Example 6.

[0029] Fig.11 This is a picture of the AM-xy@FEC sample used to measure the compressive strength in Example 7.

[0030] Fig.12 This is a comparison chart of the tensile strength, compressive strength, elastic modulus and ionic conductivity of the AM-xy@FEC obtained in Examples 5, 6 and 7.

[0031] Fig.13 1 is a comparison chart of the tensile strength, elastic modulus and ionic conductivity of the AM-xy@SN obtained in Example 5 and Example 6. DETAILED DESCRIPTION

[0032] The preparation of some in-situ phase separation copolymer solid electrolytes involved in the present invention and the performance test results are listed below, and the present invention is further described in detail, but is not limited to the listed compounds.

[0033] Example 1 is the preparation of electrolytes with different solvent systems Example 1: Succinonitrile electrolyte (IL) is used as a representative of nitrile; ethylene glycol dimethyl ether electrolyte (LDN) is used as a representative of ether; fluoroethylene carbonate electrolyte (1M LiTFSI FEC) is used as a representative of carbonate. The formula is shown in Table 1:

[0034] The following operations were all carried out in an argon atmosphere glove box. Lithium salt and solvent were added in proportion to a 20 mL brown glass bottle with a stirrer, and stirred in the dark to completely dissolve them to obtain an electrolyte.

[0035] Example 2-4 is the preparation of copolymer solid electrolyte Example 2: Preparation of copolymer solid electrolyte based on nitrile electrolyte, represented by copolymer solid electrolyte of succinonitrile electrolyte (AM-xy@SN): acrylamide (AAm) is a hard segment monomer, methoxy poly (ethylene glycol) acrylate (MPEGA) is a soft segment monomer, and the formula is shown in Table 2.

[0036]

[0037] Note: 651-CL-IL is a diluent. Since the content of the cross-linker and initiator used in the experiment is relatively small, it is difficult to directly obtain the appropriate amount. By adopting the dilution sampling method, the cross-linker and initiator are diluted into the electrolyte, and then the appropriate amount can be obtained more accurately. The following operation of taking 651-CL-LDN and 651-CL-FEC is the same as above.

[0038] The following operations were all carried out in a glove box. IL, MPEGA, and AAm were added to a 20 mL brown glass bottle with a stirring bar according to the proportions in the above table, and stirred in the dark to completely dissolve them. The diluent was added before preparing the sample or installing the battery. After it was dropped into the mold or on the lithium sheet when installing the battery, it was photoinitiated and polymerized under 365 nm ultraviolet light to obtain a copolymer solid electrolyte (AM-xy@SN).

[0039] Example 3: Preparation of copolymer solid electrolyte based on ether electrolyte (AM-xy@DME): The formulation is shown in Table 3.

[0040]

[0041] Except for the changes in the electrolyte and diluent, the remaining reagent amounts and operating steps are the same as in Example 2.

[0042] Example 4: Preparation of carbonate-based copolymer solid electrolyte (AM-xy@FEC): The formulation is shown in Table 4.

[0043]

[0044] The following operations were all carried out in a glove box: 1M LiTFSI FEC, MPEGA, and AAm were added to a 20mL brown glass bottle with a stirrer according to the proportions in the above table, heated at 80°C, and the bottle was taken out continuously to dissolve the solid on the bottle wall in the solvent to dissolve all the AAm. The diluent was added before preparing the sample or installing the battery, and after it was dropped into the mold or on the lithium sheet when installing the battery, photoinitiated polymerization was performed under 365nm ultraviolet light to obtain a copolymer solid electrolyte (AM-xy@FEC).

[0045] Example 5 is the ionic conductivity test of in-situ phase separation copolymer solid electrolyte at different temperatures in different solvent systems (ring mold) Example 5: Ionic conductivity test of AM-67@SN as an all-solid copolymer electrolyte (EIS AM-67@SN). The following test method can avoid the problem of high ionic conductivity caused by the electrolyte being compressed.

[0046] The following operation is carried out in three steps. Step 1: Use a PET film containing a single-sided hot melt adhesive to prepare a film with a thickness of about 100 μm ( l ) of the limiter ( ɸ 19*3.5mm ring), put the membrane into the 2025 type positive electrode shell, put it into a 100℃ oven, so that the mold sticks to the positive electrode shell. Step 2 (in the glove box): drip the electrolyte solution into the ring, and obtain the copolymer solid electrolyte (AM-67@SN) by ultraviolet light polymerization. After the light is over, cover the smoother side of the 1.5mm steel sheet with the electrolyte, then cover it with the shrapnel, and finally cover it with the negative electrode shell. Step 3: From room temperature (28 o C) to high temperature (80 o C) Test its impedance ( R ), and calculate its ionic conductivity (σ) according to the formula.

[0047] The contact area (S) between the copolymer solid electrolyte (AM-67@SN) and the steel sheet is 1.13 cm 2 .

[0048] The calculation formula for the test ion conductivity is: .

[0049] As attached Figure 2 The impedance diagram of AM-67@SN copolymer solid electrolyte measured at different temperatures is shown in Table 5. The ionic conductivity is obtained by calculation. It can be found that the ionic conductivity of AM-67@SN has reached 1.5 mS / cm at room temperature 28°C.

[0050]

[0051] Attached Figure 3 , Attachment Figure 4 and attached Figure 5 The graphs of ionic conductivity calculated under different solvents and temperature are shown respectively. It can be found that in addition to the high ionic conductivity of the pure soft segment, the in-situ phase-separated copolymer solid electrolytes prepared by AM-87@FEC, AM-66@SN, AM-67@SN, AM-87@SN, AM-69@LDN, AM-79@LDN, AM-88@LDN, and AM-89@LDN have high ionic conductivity.

[0052] Example 6 is a tensile strength test of in-situ phase separation copolymer solid electrolyte strips in different solvent systems.

[0053] Example 6: Tensile strength test of AM-67@SN in-situ phase-separated copolymer solid electrolyte strips.

[0054] The following operation is divided into two steps, both of which are performed in a glove box with an argon atmosphere. Step 1: drip as little electrolyte solution as possible into the mold (simulating the thickness of the electrolyte solution in the battery. If the sample is too thick, there may be some defects, which will affect the experimental results). The copolymer solid electrolyte sample (AM-67@SN) is obtained by photopolymerization through UV-light. After the light is finished, it is pushed into a sealed bag for storage. Step 2: Perform a tensile strength test.

[0055] As attached Figure 6 and attached Figure 7 It can be found that the samples prepared by AM-87@FEC, AM-67@SN, and AM-87@SN have stronger mechanical strength than those prepared by other ratios, while AM-xy@LDN is too brittle to be prepared into specimens for testing.

[0056] Example 7 is a compressive strength test of in-situ phase separation copolymer solid electrolyte samples in different solvent systems.

[0057] Example 7: Compression strength test of AM-87@FEC in-situ phase separation copolymer solid electrolyte sample.

[0058] The following operation is carried out in three steps. Step 1: Prepare several syringes and cut off a part of the needle plug near the needle stem to make a mold. Step 2 (performed in a glove box): drip about 3 mL (10 mm high) of electrolyte solution into the syringe, and use UV-light to perform photopolymerization to obtain a copolymer solid electrolyte sample (AM-87@FEC). After the illumination is completed, push it into a sealed bag for storage. Step 3: Perform a compressive strength test from a compressive strain of 0% to 50%.

[0059] As attached Fig.10 and attached Fig.11 In the experiment, the phase separation can be checked by observing the transparency of samples with different proportions. It is found that with the increase of the hard segment AAm content, the formed polymer electrolyte becomes more opaque and the transition from microscopic phase separation to macroscopic phase separation becomes more obvious.

[0060] As attached Fig.12 and attached Fig.13 It can be found that the in-situ phase-separated copolymer solid electrolytes prepared by AM-87@FEC, AM-67@SN, and AM-87@SN simultaneously achieve high ionic conductivity and high mechanical strength.

Claims

1. An in-situ phase separation copolymer solid electrolyte, characterized in that The hard segment monomer is an olefin monomer that can form a strong hydrogen bond, and the soft segment monomer is an olefin monomer containing an ether on the side group. These two monomers and lithium salt are dissolved in a solvent system, and the polymerization is initiated by heat or light in the presence of a crosslinking agent. The hard segment monomer is shown in formula (I): ; The soft segment monomer is shown in formula (II), wherein x is the number of links, ranging from 1 to 50: 。 2. The in-situ phase separation copolymer solid electrolyte according to claim 1, characterized in that: The solvent is a nitrile solvent, an ether solvent, a carbonate solvent or a phosphate solvent.

3. The in-situ phase separation copolymer solid electrolyte according to claim 1, characterized in that: The lithium salt is shown in formula (III): 。 4. The in-situ phase separation copolymer solid electrolyte according to claim 1, characterized in that: The mass percentage of the copolymer formed by the hard segment and the soft segment in the in-situ phase separation copolymer solid electrolyte is 25-90%.

5. The in-situ phase separation copolymer solid electrolyte according to claim 2, characterized in that: The hard segment monomer accounts for 5-100% of the total mass of the soft segment and hard segment monomers.

6. The in-situ phase separation copolymer solid electrolyte according to claim 1, characterized in that: The crosslinking agent contains two or more carbon-carbon double bonds.

Citation Information

Patent Citations

  • Solid electrolyte composition, binder for all-solid-state secondary batteries, and electrode sheet for batteries and all-solid-state secondary battery each using said solid electrolyte composition

    CN105580186A

  • Polymer solid electrolyte and lithium secondary battery using the same

    JP2000149658A

Cited By

  • Application of linear triblock copolymer in thermoplastic elastomer type solid polymer electrolyte and electrolyte thereof

    CN120682425A